A New System of Chemical Philosophy. Volume 1 - Dalton, John (Place of publication not identified : publisher not identified, 1808)
The chemist and meteorologist John Dalton (1766-1844) published A New System of Chemical Philosophy in two volumes, between 1808 and 1827. Dalton's discovery of the importance of the relative weight and structure of particles of a compound for explaining chemical reactions transformed atomic theory and laid the basis for much of what is modern chemistry. Volume 1 was published in two parts, in 1808 and 1810. Part 1 offers an account of Dalton's atomic theory. It contains chapters on temperature, the constitution of bodies, chemical synthesis and a number of plates including his famous table of symbols for the atoms of various elements. Part 2 contains a chapter on elementary principles and twelve sections on different groups of two-element compounds. Dalton's work is a monument of nineteenth-century chemistry. It will continue to be read and enjoyed by anybody interested in the history and development of science.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).